Working-class neighborhoods of the Junta Pro Desocupados: New ways to raise the city in Lima in the 30s - Maldonado Félix, Héctor (2010)
The peruvian urbanism in early XX century presents the end of ideals of República Aristocrática and the beginning of modern state. In this context, The Peruvian modernism urbanism is expressed by the worker housing. The Junta Departamental de Pro Desocupados de Lima created in 1931 will be make modernism urban project, the worker housing will have an area of housing and sports